Research progress of the CXCR4 mechanism in Alzheimer's disease. Issue 1 (3rd March 2022) - Wang, Qiu‐Lin; Fang, Chang‐Le; Huang, Xue‐Yan; Xue, Lu‐Lu
Abstract: Alzheimer's disease (AD) is a degenerative brain disease with complex clinical manifestations and pathogeneses such as abnormal deposition of beta‐amyloid protein and inflammation caused by the excessive activation of microglia. CXC motif chemokine receptor type 4 (CXCR4) is a type of G protein‐coupled receptor that binds to CXC motif ligand 12 (CXCL12) to activate downstream signaling pathways, such as the Janus kinase/signal transducer and activator of transcription and the renin–angiotensin system (Ras)/RAF proto‐oncogene serine (Raf)/mitogen‐activated protein kinase/extracellular‐regulated protein kinase; most of these signaling pathways are involved in inflammatory responses. CXCR4 is highly expressed in the microglia and astrocytes; this might be one of the important causes of inflammation caused by microglia and astrocytes. In this review, we summarize the mechanism and therapeutics of AD, the structures of CXCR4 and the CXCL12 ligand, and the mechanisms of CXCR4/CXCL12 that are involved in the occurrence and development of AD. The possible treatment of AD through microglia and astrocytes is also discussed, with the aim of providing a new method for the treatment of AD. Abstract : We summarize the mechanism of Alzheimer's disease (AD). We summarize the mechanism of CXC motif chemokine receptor type 4 (CXCR4)/CXC motif ligand 12 (CXCL12) and the structures of ligands CXCR4 and CXCL12, which are involved in the occurrence and development of AD. The possible treatment of AD through microglia and astrocytes is also described, with the aim of providing necessary evidence for the subsequent treatment of AD.